(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Cloud integration helps in distributing data over different cloud storage and helps applicationprograms to access and process data using different computation mechanisms. Hadoop is based on twomain modules Mapreduce for processing and generating large data sets and Hadoop Distributed FileSystem (HDFS) for storing data on distributed clusters. Hadoop has been commonly accepted in the fieldof cloud computing where resource utilization and system performance require an excellent taskscheduling mechanism. AES- 128 in ECM mode will be used to encrypt the OTP algorithm’s key, whichwill then be used to encrypt HDFS data blocks utilizing the suggested technique. Using the OTPalgorithm, we can ensure that the plaintext the asymmetric key are the same length (i.e., 128 bits).Using encryption decryption with a variety of keys, cryptographic methods are largely used to protectdata on the cloud. Hybrid-Key Stream Cipher Mechanism is a proposed method (HKSCM). Python will beused for the actual implementation of the proposed algorithm. For practical implementation we use LinuxOS, Containerization, various Clouds platforms.